ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KAYU LINGGUA PADA HOME INDUSTRI MEBEL DI DESA NANIA KOTA AMBON - Wa Asrida; Nicodemus Rahabeat (Politeknik Negeri Ambon, 2022)
This study aims to find out how to control the supply of linggua wood raw materials at the Rahmi Furniture home industry in Nania Village using the EOQ method. The results of the study show that the cost of purchasing raw materials is the same as the cost of storing raw materials so that the minimum total acceptable storage cost is IDR 1,529,965. while the economical purchase of raw materials can be made 10 times in one period and each order can order as many as 36 pieces of lingua board, resulting in very efficient costs. Keywords: control, inventory, raw materials, EOQ